2020
DOI: 10.3390/cells9051162
|View full text |Cite
|
Sign up to set email alerts
|

Homing and Engraftment of Intravenously Administered Equine Cord Blood-Derived Multipotent Mesenchymal Stromal Cells to Surgically Created Cutaneous Wound in Horses: A Pilot Project

Abstract: Limb wounds on horses are often slow to heal and are prone to developing exuberant granulation tissue (EGT) and close primarily through epithelialization, which results in a cosmetically inferior and non-durable repair. In contrast, wounds on the body heal rapidly and primarily through contraction and rarely develop EGT. Intravenous (IV) multipotent mesenchymal stromal cells (MSCs) are promising. They home and engraft to cutaneous wounds and promote healing in laboratory animals, but this has not been demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 82 publications
(138 reference statements)
0
17
0
Order By: Relevance
“…Allogeneic CB-MSCs originating from five unrelated male donor foals (eQcell Inc.; Guelph, ON, Canada) were characterized, prepared, processed, and transported overnight in full concentration HypoThermosol FRS (HTS-FRS) (BioLife Solutions, Bothell, WA, USA) in a cooler approved for transport of mammalian cells (Greenbox 2–8 °C thermal management system, ThermoSafe, Arlington Heights, IL, USA) as previously described [ 26 , 30 , 31 ]. Briefly, CB-MSCs were expanded from cryopreserved sources, and after culture showed a consistent phenotype, had trilineage differentiation capabilities, and had high expression of cluster of differentiation (CD)20, CD44, CD90, and low expression of CD4, CD8, CD11, CD73, major histocompatibility complex (MHC)-I and MHC-II [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Allogeneic CB-MSCs originating from five unrelated male donor foals (eQcell Inc.; Guelph, ON, Canada) were characterized, prepared, processed, and transported overnight in full concentration HypoThermosol FRS (HTS-FRS) (BioLife Solutions, Bothell, WA, USA) in a cooler approved for transport of mammalian cells (Greenbox 2–8 °C thermal management system, ThermoSafe, Arlington Heights, IL, USA) as previously described [ 26 , 30 , 31 ]. Briefly, CB-MSCs were expanded from cryopreserved sources, and after culture showed a consistent phenotype, had trilineage differentiation capabilities, and had high expression of cluster of differentiation (CD)20, CD44, CD90, and low expression of CD4, CD8, CD11, CD73, major histocompatibility complex (MHC)-I and MHC-II [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cells were passaged 4–5 times and cultured for 35–45 days. CB-MSCs were then harvested using trypsin and ethylenediaminetetraacetic acid, washed with phosphate-buffered saline, and pooled into a mixed population of donor cells [ 21 , 26 , 31 ]. Cells were then resuspended in HTS-FRS prior to being placed in the cooler and shipped to our laboratory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in a study on IV injection of allogeneic adipose tissue-derived MSCs, MSCs labeled with a cell membrane dye were rarely detected in the synovial fluid ( 43 ). In a rabbit and horse study, however, homing of IV injected, respectively, autologous and allogeneic MSCs to places of tissue injury was confirmed ( 70 , 71 ). Olsen et al ( 43 ) reported pulmonary trapping, to early assessment of the synovial fluid, detainment in the synovial membrane and inadequate cell labeling as possible causes of their insufficient MSC homing detection ( 43 ).…”
Section: Study Outcomesmentioning
confidence: 95%
“…Early healing was enhanced, with histology suggesting a pro-healing rather than a pro-inflammatory scenario and smaller sizes in MSC-treated wounds, with no additional advantage of hypoxic preconditioning [ 104 ]. Systemic administration of allogeneic UCB-MSCs resulted in engraftment into induced wounds on the forelimb and thorax at early stages, without clinically adverse reactions [ 105 ]. Autologous PB-SCs injected both locally and systemically in four naturally occurring chronic dermal wounds in the metatarsus, unresponsive to conventional treatments, showed positive outcomes with granulation tissue formed within four weeks, and no adverse effects were noted [ 106 ].…”
Section: Application Of Equine Mscs In Disorders Of the Integumentary Systemmentioning
confidence: 99%